Effect of the methanolic extracts of different parts of Ferula assa-foetida on naloxone-induced withdrawal behavior in morphine-dependent mice - Mahnaz Khanavi; Sajad Maadani; Behnaz Farahanikia; Mahdieh Eftekhari; Mohammad Sharifzadeh (Mashhad University of Medical Sciences, 2017)
Objective: Ferula assa-foetida, a native species in Iran, is used for treatment of several diseases particularly for neurological disorders in Iranian Traditional Medicine. The aim of this study is to investigate the effect of methanolic roots, fruits, and aerial parts extracts of Ferula assa-foetida on withdrawal syndrome in morphine-dependent mice. Materials and Methods: Aerial parts, roots, and fruits of the plant were separately extracted with 80% MeOH. For induction of dependence, morphine (50, 50 and 75 mg/kg) was injected subcutaneously three times daily (10 am, 1 pm and 4 pm) for three days and a last dose of morphine (50 mg/kg) was administrated on the fourth day. Withdrawal syndrome was induced by injection of naloxone (5 mg/kg, intraperitoneal) 2 hr after the final dose of morphine. Different doses of the extracts were administered i.p. 60 minutes before naloxone injection and withdrawal sign was recorded 2 minutes after naloxone injection for a period of 60 minutes.   Results: Pre-treatment of animals with different doses (2.5, 5, 10, 20 mg/kg) of methanolic extract of the aerial parts of F. assa-foetida caused a significant decrease in naloxone-induced behavior. Intraperitoneal administration of different doses (10, 15, 20, 25 mg/kg) of methanolic extract of the fruit significantly reduced the naloxone-induced withdrawal behavior (p